Enterococcus faecium in artisanal ripening cheese: technological and safety aspects (Research, Society and Development, 2020)
The aims of this work were to identify and characterize for some important technological properties of the E. faecium throughout the ripening process of cheese. The study involved evaluating the technological potential of six isolates of E. faecium (EFM55, EFM67, EFM9A, EFM16A, EFM19A and EFM44) from artisanal cheeses as their probiotic characteristics and technological perspective. Concerning the antimicrobial sensibility, 71% of the E. faecium tested were sensitive to all antimicrobials. No other medicine inhibited the active of E. faecium, with the exception of dipyrone for the EFM19A and EFM9A strains. The isolates showed good antagonistic activity against gram-negative, as EFM9A, EFM55 and EFM67 strais with better activity. The highest fermentation was observed in 42 ºC, showed the pH variation of 4.15 to 5.15, after 48 hours of fermentation. All isolates showed pH reduction at 20 ºC. However, all isolates produced higher titratable acidity at a temperature of 42ºC. The isolates EFM55 and EFM9A has had probiotic actived, biochemical and susceptibility parameters desirables, aim it’s technological potential in the production of dairy products.